Motivation and guided complex learning of solar geometry - Dytoc, Bronne C. (2016)
This paper discusses the integration of motivation and guided complex learning in mastering basic solar-geometry, as taught in the environmental technology course, ARCH 3314, taught in Kennesaw State University's Undergraduate Architecture Program. The rethinking of the topic's instructional strategies responds to the objectives of improved appeal, relevance, and engagement for the technical course while integrating aspects of problem-based learning and scaffolded guidance on learning complex tasks. The problem-based learning map helps in motivating the students' critical learning of solar responsive design, paving a path to a deeper appreciation of passive sustainability, while the drawing and modeling methods are quite instrumental in the guided learning of complex tasks.

Students enrolled in the course have initial introductions regarding the earth's titled relationship to the sun, and its seasonal patterns across different latitudes. The heliodon is very instrumental in transferring the reference from a celestial to a terra-centric point of view, smoothly moving to sunpath diagram exercises and applying raytracing onto orthographic drawings. The next phase in the learning is the generation of shading masks from overhangs, fins, louvers, and gridded shade solutions. Orthographic analyses of shading devices generate corresponding masks with full and half shade performance, based on how a sun could "see" it. The shading mask can now be properly oriented and overlaid onto a site's sunpath diagram that is rendered with locale's average seasonal temperatures. The juxtaposition of these two layers then allows for a relatively comprehensive evaluation of the solar shading device's performance throughout the whole year.

Having scaffolded the student's learning to appreciate and interpret the layered graphic information of sunpath, seasonal temperatures, and shading masks, they apply these skills in studio building's west facade, which performs poorly in terms of solar response. Having actual experience of these spaces contributes to their project's sense of real-world relevance to their project exercise. Student teams construct and apply their design onto a scaled model of the building. The model itself is set on a Heliodon table that turns and tilts to accurately simulate solar behavior in early and late afternoon, during spring, systematically documented; and all this accumulated information is ultimately laid out in a large poster.